Domain Walls in Curved Thin Surfaces - Altbir-Drullinsky, D; Corona-Gonzalez, R (Elsevier B.V., 2020)
In this paper, by means of analytical calculations and a simple model, we studied the effect of curvature in magnetic thin stripes. Three different domain walls were observed, depending on the slab geometry. A phase diagram that shows the geometric parameters at which each domain wall is preferred was obtained. The presented methodology can also be used to obtain the magnetization behavior in other curved structures with proper aspect ratio relations. © 2019 Elsevier B.V.